2019
DOI: 10.1111/gbb.12548
|View full text |Cite
|
Sign up to set email alerts
|

Congenital facial palsy and emotion processing: The case of Moebius syndrome

Abstract: According to the Darwinian perspective, facial expressions of emotions evolved to quickly communicate emotional states and would serve adaptive functions that promote social interactions. Embodied cognition theories suggest that we understand others' emotions by reproducing the perceived expression in our own facial musculature (facial mimicry) and the mere observation of a facial expression can evoke the corresponding emotion in the perceivers. Consequently, the inability to form facial expressions would affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 189 publications
(437 reference statements)
3
47
1
1
Order By: Relevance
“…However, this interpretation seems unlikely given the absence of group differences in reaction times. Also another study employing a labeling task showed that Moebius children and controls show similar latency response (De Stefani et al 2019) thus supporting the idea that general visuocognitive impairments are not present in these patients. We cannot currently rule out this potential alternative explanation of our results.…”
mentioning
confidence: 56%
See 3 more Smart Citations
“…However, this interpretation seems unlikely given the absence of group differences in reaction times. Also another study employing a labeling task showed that Moebius children and controls show similar latency response (De Stefani et al 2019) thus supporting the idea that general visuocognitive impairments are not present in these patients. We cannot currently rule out this potential alternative explanation of our results.…”
mentioning
confidence: 56%
“…Other studies, using labeling paradigms, have reported that Moebius children show deficits not only in autonomic responses to emotional stimuli but also in categorizing facial expressions (Nicolini et al 2019;De Stefani et al 2019), as predicted by sensorimotor simulation models. The conclusions of our and other studies seem to contrast with two previous studies in which either a deficit of recognition/discrimination of facial expressions of emotions was not observed in Moebius participants (Bogart and Matsumoto, 2010) or, using a single-VWM deficits in Moebius subjects -Gambarota et al…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In line with this proposal, neuroimaging techniques have shown that (pre)motor and somatosensory regions representing the face are active during the perception of emotional face [32][33][34][35], and neural activity in these regions correlates with the degree of facial mimicry [36][37][38]. Moreover, damage to, or transcranial magnetic stimulation (TMS) interference with, the face representations in motor and somatosensory areas disrupts facial mimicry and impairs the recognition and interpretation of emotional expressions [39][40][41][42][43][44] (see also [45]). Furthermore, sensorimotor simulation would in turn affect theory of mind and emotion-related regions including the amygdala and the insula [31], especially for dynamic emotional stimuli [46,47].…”
Section: Introductionmentioning
confidence: 86%